2007
DOI: 10.2143/ac.62.1.2019365
|View full text |Cite
|
Sign up to set email alerts
|

Right and left ventricular adaptation to training determined by conventional echocardiography and tissue Doppler imaging in young endurance athletes

Abstract: Our study shows that despite an increase in left and right ventricular mass indexes, the LVMI/RVMI ratio stays stable. Training results in a better systolic and diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Cross-sectional or flow propagation data from TDI studies tend to mirror the Doppler flow data described above, with limited differences in E 0 (Caso et al 2000;Schmidt-Trucksäss et al 2001;Pelà et al 2004;Baldi et al 2003), A 0 being similar or lower (Caso et al 2000;Schmidt-Trucksäss et al 2001;Pelà et al 2004;Tümüklü et al 2008;Kasikcioglu et al 2005;Zoncu et al 2002) and generally small improvement in the E 0 /A 0 ratio in athletes compared to untrained subjects. Nonetheless, studies of Olympic speed skaters (Poh et al 2008), professional soccer players (Tümüklü et al 2008) and endurance trained individuals (Vinereanu et al 2002;Zoncu et al 2002;Nottin et al 2004;Kasikcioglu et al 2005;Palka et al 1999;Poulsen et al 2007;Koç et al 2007) have reported elevated tissue Doppler measures of E 0 , E 0 /A 0 or Vp.…”
Section: Impact Of Exercise Training On Diastolic Function: Cross-secmentioning
confidence: 99%
“…Cross-sectional or flow propagation data from TDI studies tend to mirror the Doppler flow data described above, with limited differences in E 0 (Caso et al 2000;Schmidt-Trucksäss et al 2001;Pelà et al 2004;Baldi et al 2003), A 0 being similar or lower (Caso et al 2000;Schmidt-Trucksäss et al 2001;Pelà et al 2004;Tümüklü et al 2008;Kasikcioglu et al 2005;Zoncu et al 2002) and generally small improvement in the E 0 /A 0 ratio in athletes compared to untrained subjects. Nonetheless, studies of Olympic speed skaters (Poh et al 2008), professional soccer players (Tümüklü et al 2008) and endurance trained individuals (Vinereanu et al 2002;Zoncu et al 2002;Nottin et al 2004;Kasikcioglu et al 2005;Palka et al 1999;Poulsen et al 2007;Koç et al 2007) have reported elevated tissue Doppler measures of E 0 , E 0 /A 0 or Vp.…”
Section: Impact Of Exercise Training On Diastolic Function: Cross-secmentioning
confidence: 99%
“…While both male and female highly trained athletes display marked adaptive changes of cardiac morphology and function, e.g., increased left ventricular wall thickness and end‐diastolic diameter, women generally exhibit lesser changes than men, and the characteristics and temporal development of these adaptations in sedentary women subjected to different types of aerobic training have not been clearly defined (Wolfe et al, 1992; George et al, 1995, 1999; Pelliccia et al, 1996; Pluim et al, 2000; Slørdahl et al, 2004). Furthermore, previous reports have generally focused on training‐induced changes in conventional echocardiographic measures of the left ventricular geometry and the global systolic function, while recent interest has centered on the use of tissue Doppler imaging to assess more subtle changes of cardiac function that may carry prognostic information (Koç et al, 2007; Krieg et al, 2007; Poulsen et al, 2007; Møgelvang et al, 2009).…”
mentioning
confidence: 99%
“…Estas son algunas de las razones por las que en la actualidad es un examen de segunda línea, en pacientes con algún hallazgo en el screening y en pacientes con antecedentes familiares de cardiopatías y SDMS 2,22,29,31,33,53 .…”
Section: Ecocardiografíaunclassified
“…Sabemos que la MCH es la principal causa de SDMS, sin embargo existe una entidad, cada vez mejor descrita, que se presenta en deportistas entrenados denominada corazón de atleta. Esta presenta características muy similares a las encontradas en MCH desde el punto de vista ecográfico 1,53,58,61 . Se describe especialmente en deportistas de alta competencia o deportistas que hacen deportes isométricos (p.e.…”
Section: Corazón De Atletaunclassified
See 1 more Smart Citation